Ombudsman, Public, Role Peran Lembaga Ombudsman Republik Indonesia dalam Meningkatkan Kualitas Pelayanan Publik - Nazwa Aisyarah Rafi; Nadia Dewangga; Khoirul Anwar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to analyze the role of the Ombudsman of the Republic of Indonesia (ORI) in improving the quality of public services and strengthening public trust in the government. In line with the importance of quality public services, this study focuses on how the Ombudsman supervises government agencies and its impact on transparency and accountability of public services. In addition, this study also explores the challenges faced by the Ombudsman in carrying out its duties. The research method used is a descriptive qualitative approach, with data collection techniques of literature studies and analysis of official Ombudsman documents. This secondary data is used to understand the role of the Ombudsman in improving the quality of public services and to analyze the influence of the Ombudsman's recommendations on government agencies. Data analysis was carried out using thematic analysis techniques to identify themes related to supervision, recommendations, and the impact of the Ombudsman on public services. The results of the study indicate that the Ombudsman of the Republic of Indonesia has a significant role in improving the quality of public services by supervising, providing recommendations, and resolving disputes between the community and government agencies. However, challenges such as limited resources, bureaucratic obstacles, and low public awareness hinder its effectiveness. Nevertheless, the Ombudsman's recommendations contribute to improving the quality of service and increasing public trust in the government.